2017
DOI: 10.9734/ajob/2017/36542
|View full text |Cite
|
Sign up to set email alerts
|

Libido Enhancement Potential of Piper guineense in Male Wistar Rats

Abstract: Background: Some spices have been reported to play contributory role in enhancing male reproductive function. Aims: To determine the effect of Piper guineense consumption on some libido indices and behavioral pattern of male Wistar rats at different concentrations. Study Design: This is a Cross-sectional nonclinical study in animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…In this study, there was an observed loss of appetite, sluggishness, passive behavior, prolonged response to external stimuli, and a color change in feces, which was agreed upon [24] . Those findings might have led to the retarded growth and weight loss recorded in this research.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, there was an observed loss of appetite, sluggishness, passive behavior, prolonged response to external stimuli, and a color change in feces, which was agreed upon [24] . Those findings might have led to the retarded growth and weight loss recorded in this research.…”
Section: Discussionsupporting
confidence: 78%
“…Aphrodisiac potentials: Using parameters such as penile erection index, copulatory behaviour and orientation activities towards themselves (genital grooming) and female rats (anogenital sniffing, mounting), aqueous extracts of P. guineense modified the sexual behaviour of male rats by increasing sexual arousal (Kamtchouing et al 2002). Memudu et al, (2015) and Ochei et al, (2017) also investigated the aphrodisiac potentials of this plant and obtained results similar to that of Kamtchouing et al, (2002).…”
Section: Phytochemical Constituent Of Piper Guineensesupporting
confidence: 62%